REFORMULASI FIQH MUAMALAH TERHADAP PENGEMBANGAN PRODUK PERBANKAN SYARIAH - Aryanti, Yosi (JURIS (Jurnal Ilmiah Syariah), 2017)
This study aims to describe the reformulation of fiqh muamalah in order to provide innovation to the products of sharia banking. This research is a library study. Data of the research was obtained from secondary sources which were taken from library materials, such as fiqh, literature, legislation, official document, result of previous research, article, magazine, newspaper, and other sources related to this research . Secondary data is sourced from the primary legal materials in the form of regulations relating to sharia banking. The results showed that: 1) In reformulation of fiqh muamalah required a number of tools and disciplines of sharia as well as some moral principles for the formulation according to sharia and are in the corridor of sharia. The disciplines are ushul fiqh, qawaid fiqh, tasyrik talaq, tasyrik philosophy and maqashid syariah, 2) Fiqh muamalah reformulated through several methods ijtihad, namely ijtihad intiqa'I, ijtihad insya'I, and ijtihad komparasi, and 3) success the future syari'ah banking system will depend a lot on innovation development. This is marked by the ability of syari'ah banks to present attractive, competitive products and facilitate transactions, in accordance with the needs of the community.